PRINCIPAL MANAGEMENT IN FOSTERING STUDENT INDEPENDENCE AT SMK MA’ARIF NU CILONGOK, BANYUMAS - Nurkholis Nurkholis (Jurnal Konseling Pendidikan Islam, 2026)
This study was conducted at SMK Ma’arif NU 1 Cilongok, Banyumas Regency, with the aim of understanding and obtaining an overview of the principal’s management practices in fostering student independence. Research data were collected from respondents through observation, interviews, and documentation. To ensure data validity, a triangulation technique was employed, encompassing sources, theory, and time. Data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions or verification. The results of the study indicate that student independence management at this school aligns with the school’s vision and mission, which include: (1) educational management in school administration to support student independence programs, (2) the implementation of student independence programs, and (3) the dissemination of the program through the principal, teachers, and educational staff.